2009
DOI: 10.1603/008.102.0621
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of the Galeal Styloconic Sensilla of Larval Lymantria dispar (Lepidoptera: Lymantriidae)

Abstract: Lepidopteran larvae possess two pairs of styloconic sensilla located on the maxillary galea. These sensilla, namely the lateral and medial styloconic sensilla, are each comprised of a smaller cone, which is inserted into a style. They are thought to play an important role in host-plant selection and are the main organs involved in feeding. Ultrastructural examination of these sensilla of fifth instar Lymantria dispar (L.) larvae reveal that they are each approximately 70 um in length and 30 um in width. Each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Generally, their morphology including a socketed conic tip inserted into the large peg was similar to that of corresponding sensilla formerly described in other lepidopteran species [5], [7], [9]–[12], [14], [15], [17], [18]. The significant difference in size between the pegs of the two sensilla styloconica, as found here, has not been reported previously, however.…”
Section: Discussionsupporting
confidence: 87%
“…Generally, their morphology including a socketed conic tip inserted into the large peg was similar to that of corresponding sensilla formerly described in other lepidopteran species [5], [7], [9]–[12], [14], [15], [17], [18]. The significant difference in size between the pegs of the two sensilla styloconica, as found here, has not been reported previously, however.…”
Section: Discussionsupporting
confidence: 87%
“…Also, the characteristic arrangement of the socketed conic tip inserted into the large peg is in correspondence to previous findings in other lepidopterous caterpillars [5,[22][23][24][25][26][27][28][29], indicating a conservative morphology of sensilla styloconica over lepidopterous species. Interestingly, the different size of the two sensilla in H. assulta, the medial being significantly longer than the lateral, is in accordance with our previous findings on H. armigera [14].…”
Section: Morphology Of Sensilla Styloconicasupporting
confidence: 90%
“…Both light and electron microscopy have shown that each sensillum styloconica is innervated by five bipolar neurons, three or four of which function as gustatory receptor neurons (GRNs) and one as a mechanosensitive neuron [5][6][7]. The GRNs in lepidopterous insects have been reported to detect distinct stimuli such as nutrients, stimulants, and deterrents, and to show different response patterns [5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The two sensilla styloconica seem to play a particularly important role in acceptance of host plants (Schoonhoven 1987). Each styloconic sensillum houses four gustatory receptor neurons (GRNs) with specific response spectra for plant compounds (summarized by Schoonhoven and Van Loon 2002; Shields 2009). Typically, some of the neurons respond to phagostimulants, primary plant metabolites like sugars and amino acids that evoke feeding.…”
Section: Introductionmentioning
confidence: 99%